2017
DOI: 10.1515/fhep-2016-0007
|View full text |Cite
|
Sign up to set email alerts
|

The Price Elasticity of Specialty Drug Use: Evidence from Cancer Patients in Medicare Part D

Abstract: Specialty drugs can bring substantial benefits to patients with debilitating conditions, such as cancer, but their costs are very high. Insurers/payers have increased patient cost-sharing for specialty drugs to manage specialty drug spending. We utilized Medicare Part D plan formulary data to create the initial price (cost-sharing in the initial coverage phase in Part D), and estimated the total demand (both on- and off-label uses) for specialty cancer drugs among elderly Medicare Part D enrollees with no low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…25 High OOP expenditures have been associated with decreased TKI access in patients with CML [9][10][11] and also across various cancers that are treated with specialty cancer drugs or oral cancer therapies. [26][27][28][29][30] High OOP expenditures will likely price-out patients whose treatment cost is a large proportion or exceeds income, thus leading to disparities in TKI access.…”
Section: Discussionmentioning
confidence: 99%
“…25 High OOP expenditures have been associated with decreased TKI access in patients with CML [9][10][11] and also across various cancers that are treated with specialty cancer drugs or oral cancer therapies. [26][27][28][29][30] High OOP expenditures will likely price-out patients whose treatment cost is a large proportion or exceeds income, thus leading to disparities in TKI access.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, we did not analyze oral cancer drugs covered by Medicare Part D because physicians do not generate profit or revenue from prescribing oral agents. Jung, Feldman, and McBean () reported that Parts B and D cancer drugs are not substitutes. However, substitution by integrated doctors would imply that the integration effect in our analysis is underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…It also allows us to avoid potential selection that a hospital's having 340B status itself changes the hospital's patient risk: When 340B hospitals develop affiliation with clinics, their patient risk changes because patients from affiliated clinics are moved to the hospitals’ outpatient departments. Accounting for this issue is important because patient risk differs between HOPDs and Offices: for example, the distribution of cancer types differs between the two settings (Avalere Health, ) and patterns of cancer drug use/spending differ by cancer type (Jung, Feldman, and McBean ). However, changes in patient risk in 340B hospitals were not properly addressed in prior work based on a hospital‐level identification approach (Government Accountability Office ; Desai and McWilliams ).…”
Section: Methodsmentioning
confidence: 99%